Solvothermal Growth of PbBi2Se4 Nano‐Flowers: A Material for Humidity Sensor and Photodetector Applications. Issue 11 (4th April 2019) - Aher, Rahul; Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Naik, Dhirsing; Vairale, Priti; Karpe, Smita; Late, Dattatray; Prasad, Mohit; Jadkar, Sandesh
Abstract : In the present work, lead bismuth selenide (PbBi2 Se4 ) nano‐flowers are synthesized by using a simple solvothermal method. Humidity sensor and photodetector based on PbBi2 Se4 nano‐flowers are fabricated on indium tin oxide (ITO) substrates and their sensing properties are investigated. Formation of PbBi2 Se4 is confirmed by XRD, EDS, and XPS whereas formation of nano‐flowers is confirmed by SEM and TEM analysis. XRD analysis reveals the hexagonal crystal structure of PbBi2 Se4 phase with a = b = 4.22 Å, and c = 17.42 Å. The surface morphology of PbBi2 Se4 clearly shows the formation of well‐organized flower‐like nanostructures which closely resembles the shape of Dahlia. The elemental mapping of chemical constituents obtained from SEM‐EDS analysis shows uniform distribution of chemical constituents for the Pb, Bi, and Se in PbBi2 Se4 nano‐flowers. The PbBi2 Se4 nano‐flowers‐based humidity sensor has a typical response time of ≈65 s and recovery time of ≈75 s. In case of PbBi2 Se4 nano‐flowers‐based photodetector, the response and recovery time are observed ≈121 and ≈123 s, respectively, under visible light illumination with photoresponsivity (5 × 10 −6 ), photosensitivity (2.16%), and quantum efficiency (1.5 × 10 4 ). The obtained results demonstrate the potential applications of solvothermally grown PbBi2 Se4 nano‐flowers‐based devices for humidity sensors and photodetectors. The ease of the present work is to develop novel material to obtain device quality humidity sensors and photodetectors. Abstract : A simple solvothermal method is used to synthesize lead bismuth selenide (PbBi2 Se4 ) nano‐flowers. PbBi2 Se4 nano‐flowers‐based humidity sensor has a typical response and recovery time of ≈65 and ≈75 s, respectively. For photodetector, the response and recovery time is ≈121 and ≈123 s under visible light with photoresponsivity (5 × 10 −6 ), photosensitivity (2.16%), and quantum efficiency (1.5 × 10 4 ).